Empirical Analysis of the Reflection of Oil Prices on Inflation in Türkiye - Kandemir Comoğlu, Gözde; Huseynli, Bahman (International Journal of Energy Economics and Policy, 2025)
Changes experienced during the globalization process also have an impact on oil prices. As a matter of fact, the change in oil prices also affects the increase in the general levels of prices. It is inevitable that we will see the measurement of these price changes in the countries most dependent on imports. In this context, Turkey, which is the sample country discussed within the framework of this study, is a country dependent on imports in terms of oil, making increases in the general levels of inflation in this country inevitable. Considered from this framework, the study investigated the relationship between oil prices and inflation for the 2004-2022 period through causality analysis. As a result of the analysis, a positive relationship was determined from oil prices to inflation. In addition, according to the results of the Granger causality test, it was determined that inflation was not the Granger cause of oil prices. In other words, within the framework of this country, the relationship between both variables is one-sided.